2008
DOI: 10.1038/modpathol.2008.71
|View full text |Cite|
|
Sign up to set email alerts
|

Automated detection of genetic abnormalities combined with cytology in sputum is a sensitive predictor of lung cancer

Abstract: Detection of lung cancer by sputum cytology has low sensitivity but is noninvasive and, if improved, could be a powerful tool for early lung cancer detection. To evaluate whether the accuracy of diagnosing lung cancer by evaluating sputa for cytologic atypia and genetic abnormalities is greater than that of conventional cytology alone, automated scoring of genetic abnormalities for 3p22.1 and 10q22.3 (SP-A) by fluorescence in situ hybridization (FISH) and conventional cytology was done on sputa from 35 subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 20 publications
(33 reference statements)
1
36
0
Order By: Relevance
“…23,24 Several attempts have been undertaken to use automated and semiautomated systems for the detection of cancer cells and dysplastic cells in sputum based on morphologic features of abnormal cell clusters, 25 ploidy measurements, [26][27][28][29][30] or the detection of genetic abnormalities with fluorescence in situ hybridization. 31 The majority of these studies reported very high sensitivities; however, we await the confirmation of the results from large-scale clinical trials. Recent technical developments have made it possible to combine flow cytometry with CT on the cellular level, allowing for cytometry in 3 dimensions.…”
Section: Discussionmentioning
confidence: 99%
“…23,24 Several attempts have been undertaken to use automated and semiautomated systems for the detection of cancer cells and dysplastic cells in sputum based on morphologic features of abnormal cell clusters, 25 ploidy measurements, [26][27][28][29][30] or the detection of genetic abnormalities with fluorescence in situ hybridization. 31 The majority of these studies reported very high sensitivities; however, we await the confirmation of the results from large-scale clinical trials. Recent technical developments have made it possible to combine flow cytometry with CT on the cellular level, allowing for cytometry in 3 dimensions.…”
Section: Discussionmentioning
confidence: 99%
“…This study extends our previous research efforts to develop noninvasive or minimally invasive diagnostic means for lung cancer. 16,[20][21][22] Given the expenses associated with quantitative molecular analysis of multiple genes by a RT-qPCR platform, a marker panel with the smallest number of miRNAs and highest diagnostic accuracy would provide a cost-effective assay for squamous cell carcinoma of lung cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Sputum was collected from the participants as described in our recent reports. 16,[20][21][22] To further validate the identified sputum markers, we collected sputum specimens from an independent set of 67 lung squamous cell carcinoma patients and 55 healthy controls. The demographic and clinical characteristics of the cancer patients are summarized in Table 1.…”
Section: Patients and Clinical Specimensmentioning
confidence: 99%
“…Several studies indicate that abnormal sputum cells, in particular identifying genetic alterations associated with malignant transformation, may be useful in identifying individuals at high risk of lung cancer (24)(25)(26)(27)(28). Several studies have reported that SDIC and automated SDIC improve sensitivity of detection of lung cancer over conventional pathology-based cytology and suggest that SDIC might be useful for early detection of lung cancer (24,(29)(30)(31)(32)(33)(34)(35).…”
Section: Introductionmentioning
confidence: 99%